Preliminary investigation of the C-terminal mutations that cause malignant hyperthermia : a thesis presented to Massey University in partial fulfilment of the requirements for the degree of Master of Science in Biochemistry - Jones, Angela Marie (Massey University, 2000)
Malignant hyperthermia (MH) is a genetic disorder characterised by abnormal muscle contractures, hypermetabolism and hyperthermia. It is referred to as 'malignant' as it can lead to death when under anaesthetic if not recognised and treated immediately. The molecular basis of MH is an abnormality in the calcium release mechanism of the sarcoplasmic reticulum. Abnormal calcium release causes the physiological symptoms of an MH crisis. Genetic linkage studies have led to the identification of the ryanodine receptor/Ca2+ -release channel as a causative factor in MH. The ryanodine receptor is a large protein which is regulated by a number of ligands including Ca2+ , Mg2+ , ATP, ryanodine and calmodulin. Most mutations in the ryanodine receptor gene that cause MH are located near two main regulatory regions on the receptor. Three mutations have recently been identified that are located in the regulatory region of the C-terminal domain. The biochemical properties of one of these mutations have been studied. The current research project began to investigate the biochemical characteristics of the other two mutations in the C-terminal domain in relation to their ryanodine binding and calcium release properties. Sarcoplasmic reticulum vesicles were isolated from skeletal muscle samples, and an attempt to identify ryanodine receptors by 3 H-ryanodine binding was made. RT-CR using RNA extracted from a skeletal muscle sample was used to construct the cDNA for the C-terminal transmembrane domain of the ryanodine receptor. This cDNA was cloned into a mammalian expression vector and introduced into COS cells. RT-PCR was also used to produce the cDNA encoding a small polypeptide to an antigenic region in the C-terminal domain of the ryanodine receptor for the preparation of antibodies. Although it appeared that there may have been ryanodine receptors in the SR vesicle preparation as determined by immunoblotting, 3 H-Ry binding to the ryanodine receptors was unable to confirm the presence of the receptors in the SR vesicles. Initial expression studies of the C-terminal domain in COS cells were inconclusive. Partial cleavage of a small antigenic polypeptide was obtained which could be used to produce antibodies to the C‍terminal domain of the ryanodine receptor.
Keywords: Malignant hyperthermia; Genetic aspects; Calcium channels; Ryanodine - Receptors